Cho hàm số (y = (x^3) - 3x + 1). Tìm khẳng định đúng.

Lưu lại

Cho hàm số $y = {x^3} - 3x + 1$. Tìm khẳng định đúng.

Đáp án: C

$y = {x^3} - 3x + 1$

TXĐ: $D = \mathbb{R}$

$\begin{array}{l}y' = 3{x^2} - 3\\y' = 0 \Rightarrow 3{x^2} - 3 = 0\\ \Leftrightarrow \left[ \begin{array}{l}x = 1\\x =  - 1\end{array} \right.\end{array}$

$y = {x^3} - 3x + 1$

TXĐ: $D = \mathbb{R}$

$\begin{array}{l}y' = 3{x^2} - 3\\y' = 0 \Rightarrow 3{x^2} - 3 = 0\\ \Leftrightarrow \left[ \begin{array}{l}x = 1\\x =  - 1\end{array} \right.\end{array}$



Vậy, hàm số đồng biến trên $\left( { - \infty , - 1} \right)$ và $\left( {1, + \infty } \right)$

Vậy, hàm số đồng biến trên $\left( { - \infty , - 1} \right)$ và $\left( {1, + \infty } \right)$

TOP THÀNH VIÊN NỔI BẬT

    Xem top 100 thành viên